RNA interference of STAT6 rapidly attenuates ongoing interleukin-13-mediated events in lung epithelial cells - William Walker (Immunology, 2009)
Signal transducer and activator of transcription 6 (STAT6) expression in lung epithelial cells plays a central role in asthma pathogenesis, with its activation driving the development of airway hyper-reactivity and local inflammation. Therefore, inhibition of local STAT6 expression provides a rationale for therapeutic intervention in bronchial asthma. Given the absence of specific inhibitory drugs, we tested the ability of small interfering RNAs (siRNAs) to target STAT6 gene expression through the molecular process of RNA interference (RNAi). At pico-molar concentrations, STAT6-specific siRNAs potently inhibited STAT6 mRNA expression in lung epithelial cells (50% inhibitory concentration range = 134-861 pm) without inducing cellular interferon responses. Detectable STAT6 protein expression was rapidly abolished within 48 hr of treatment (t(1/2) range = or < 12-37 hr) and this was unaffected by pretreatment with STAT6-activating cytokines. Furthermore, STAT6 suppression by RNAi produced downstream functional inhibitory effects in that interleukin (IL)-13- or IL-4-driven eotaxin chemokine family [chemokine (C-C motif) ligand 11 (CCL11), CCL24 and CCL26] mRNA expression was markedly inhibited. Induction of detectable CCL26 protein synthesis was completely ablated by pretreating cells with STAT6-specific siRNA. The therapeutic potential of this approach is further demonstrated by novel findings that cells pre-exposed to IL-13 or IL-4 and subsequently treated with STAT6-targeting siRNA exhibited a rapid and significant attenuation of ongoing CCL26 protein expression, suggesting that chronic asthma-associated lung inflammation will be responsive to this approach.